An Exploratory Study of Labor Trafficking Among U.S. Citizen Victims, 2019-2020 - Dank, Meredith ([Verlag nicht ermittelbar], 2024)
Recent research has identified numerous challenges facing victims of labor trafficking in the U.S. (Owens, et al., 2014; Brennan, 2014). Most of the research on labor trafficking occurring in the U.S., however, has focused on the experiences of non-citizen and foreign national victims. There are many reasons to suspect that labor trafficking victimization occurs among U.S. citizens, although the identification of this phenomenon has been difficult. For example, the homeless and those with insecure housing, individuals with intellectual and physical disability, low-wage and transitional workers, and those working in illicit economic markets or within sexualized labor services are anticipated to be at higher risk for labor trafficking victimization. In this exploratory mixed-methods study, the research team answered four main questions to help illuminate the phenomenon of labor trafficking of U.S. citizens. What are the personal, economic, or structural vulnerabilities that put U.S. citizens at risk for labor trafficking? What does labor trafficking looks like for U.S. citizens and where does it fall on a continuum of labor exploitation? How are U.S. citizens recruited into, move to, experience, and escape from labor trafficking victimization? How do U.S. citizen labor trafficking victims seek help or exit exploitative labor situations? These questions were answered through surveys with individuals at high risk for labor trafficking victimization across four U.S. sites (n=240), individual interviews with a subsample of survey respondents (n=27), and interviews with service providers (n=20). The surveyed population were citizens who were born in the U.S., those who were naturalized citizens at the time of their victimization, and legal permanent residents. The sampling strategy relied on several snowball and purposive sampling techniques and were developed in partnership with social service agencies, government agencies, and community contacts with knowledge of or contact with labor trafficking in each of the sites. As such, the study was not designed to generate prevalence estimation or to claim any representativeness of labor trafficking violations among U.S. citizens. This collection only includes the quantitative survey data. Qualitative interview data are not available.